Recognition Levels of Physics Laboratory Tools for Ninth Class Students - Hasan Şahin Kızılcık; Sultan Çağan; Pervin Ünlü Yavaş (Elementary Education Online, 2023)
The purpose of this study is to determine how well the students who started the course knew the laboratory tools in the physics laboratory during their previous school life. The research was conducted by screening method. In the study, 28 pieces of laboratory tool which are used in the physics laboratories and expected to be known by the students were selected. The laboratory tools were shown to the students and they were asked to examine them. Students are asked to write a form with the fields where they can write the name and the function of them as open ended. In the form, they were also asked whether they had previously seen the laboratory tools and whether they had made any experiments using this tool before. The number of students who came from Turkey’s several provinces and began a high school in Ankara to the 9th grade is 109. Students were asked to write to the form whether exists a physics laboratory in their secondary schools. According to the results, most students do not recognize the laboratory tools. Among the students, the number of laboratory tools that he/she does not know the name of them is 17, and the function of them is 18. The number of laboratory tools are correctly named by more than 50% of the students is only 7, and only 3 functions of them are known correctly. 17 of the tools were never seen before by more than 50% of the students and they had never experimented with 25 of the tools. There is a significant relationship between students’ knowledge of the name and function of a tool and the fact that they had seen and experimented with the tool before. There is a significant difference between knowing the function of the tool and existence of laboratory in secondary school.